3, 4-Methylenedioxymethamphetamine (MDMA; ecstasy) use and transitions to injection drug use among street-involved youth. Issue 3 (3rd July 2019) - Lake, Stephanie; Gaddis, Andrew; Tupper, Kenneth W.; Nosova, Ekaterina; DeBeck, Kora
Abstract: Background: Despite the popularity of 3, 4-methylenedioxymethamphetamine (MDMA; ecstasy) among young people across North America and Europe, MDMA is rarely explored in studies of young people at high risk of injecting drugs. We conducted a study among street-involved youth who use illicit drugs in Vancouver, Canada, to understand if use of MDMA is associated with initiation of injection drugs. Methods: We followed injection-naïve participants in the At-Risk Youth Study (ARYS), an ongoing prospective cohort of street-involved youth aged 14–26 who use illicit drugs. Bivariate and multivariate extended Cox models with time-updated variables were used to examine the association between MDMA use and initiation of injection drug use between September 2005 and May 2015. Results: Among 483 youth, 306 (63.4%) had a history of MDMA use and 218 (45.1%) had used MDMA in the previous 6 months at baseline. A total of 105 (21.7%) youth initiated injection drug use over the 10-year period, yielding an incidence density of 8.51 (95% confidence interval [CI]: 6.96–10.30) per 100 person-years. MDMA use was not significantly associated with initiating injection drugs at the bivariate (hazard ratio: 0.93, 95% CI: 0.61–1.42) or multivariate (adjusted hazard ratio: 0.88, 95% CI: 0.57–1.35) level, after adjusting for socio-demographic and substance use confounders. Conclusions: Amid ongoing frequent use of MDMA among some young people in North America, we did not observe an elevated risk of injection initiation among those who used MDMA in this cohort of street-involved youth.